MANAJEMEN PENYELENGGARAAN IBADAH HAJI - Dalinur M. Nur (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2020)
Professional and accountable management is a probem solving of complex problems around the implementation of Hajj. Hajj management is a process of organizing or managing Hajj activities by using management functions that include planning, organizing, actuating, controlling, and evaluating, so that the pilgrimage is carried out effectively and efficiently. Hajj is a process, method, and act of organizing or carrying out a series of Hajj activities that include guidance, service, protection, and implementation of the Hajj. Hajj guidance is a series of activities that include information, counseling, and guidance, on the pilgrimage. Services include all activities to provide services to all prospective pilgrims and pilgrims, from registration to returning to the country, including transportation, accommodation and health services. Protection is the efforts made by the government to ensure the safety and comfort of pilgrims which includes maintaining the safety of pilgrims while in Saudi Arabia and safeguarding the items of pilgrims while in boarding. Key Words: Management, Hajj